Improvement and Implementation of Sustainable Key Performance Indicators in Supply Chain Management: The Case of a Furniture Firm - Yuksel Yurtay; Nilufer Yurtay; Huseyin Demirci; Esin Ayse Zaimoglu; Alper Goksu (IEEE Access, 2023)
Businesses today recognize the importance of business performance management (BPM) as an effective business strategy and practical solution to a robust supply chain management process. At the same time, businesses seek to deepen their footprints in global markets, to actively use critical metrics, KPIs (Key Performance Indicators), in business performance management, to make performance management compatible with strategic goals, up-to-date and sustainable. KPIs are priority indicators determined to achieve the strategic objectives of the enterprise. Updating the KPIs used to measure, monitor and analyze business performance also has a critical place in performance management. This article presents a case study of a novel approach to real-time updating and monitoring KPIs integrated into supply chain management (SCM) software. The proposed approach bridges the gap between measuring and implementing business performance. The study analyzes and aligns the relationships of duplicate KPIs. It systematically carries out the KPI weights of the managers in line with the strategic goals and improves performance management by eliminating the weakness in the KPI change. It also provides a framework for sustainable performance management and discusses the case study with implications of KPIs that affect performance management success.